Gender Gaps in Political Careers: Evidence from Competitive Elections - Davide Cipullo (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This paper investigates the impact of voter support on the representation of women in the political profession. The empirical analysis exploits two-stage elections in the United States and Italy to hold the selection of candidates constant. In two-stage elections, candidates are admitted to the second round of voting based on the outcome of the first round. I find that among candidates who marginally qualify for the final round, women are 20 percent less likely than men to be elected to the US House of Representatives and 40 percent less likely to be elected mayor in Italian municipalities. Using a difference-in-discontinuities design, I then show that the gender gap in the probability of being elected has long-lasting effects on career trajectories. Women are substantially less likely than men to win future elections and to climb the political hierarchy. My findings suggest that one of the reasons that few women reach the top in politics is that female candidates face hurdles at the beginning of their careers.
Keywords: C24; D02; D72; J16; 330; gender gaps; self-selection; political careers; voting